2010
DOI: 10.2147/ijwh.s8550
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of pre-eclampsia: an update

Abstract: Pre-eclampsia is a significant, multifactorial, multiorgan disease affecting 5%–8% of all pregnancies in the US where it is the third leading cause of maternal mortality. Despite improvements in the diagnosis and management of pre-eclampsia, severe complications can occur in both the mother and the fetus, and there is no effective method of prevention. Early detection and identification of pregnant women most at risk of developing the disease have proven challenging, but recent efforts combining biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 56 publications
(86 reference statements)
1
113
0
12
Order By: Relevance
“…9 It was widely demonstrated that gestational age at birth had a major impact on perinatal outcome. 10 Perinatal mortality and morbidity were demonstrated to be higher in women with EO-PE.…”
Section: Discussionmentioning
confidence: 99%
“…9 It was widely demonstrated that gestational age at birth had a major impact on perinatal outcome. 10 Perinatal mortality and morbidity were demonstrated to be higher in women with EO-PE.…”
Section: Discussionmentioning
confidence: 99%
“…At the first prenatal visit, it is possible to identify several factors that have been proven to increase the risk of preeclampsia development (see Tab. III) (24,(46)(47)(48)(49). The detection of pregnant women at high risk for preeclampsia involves tighter monitoring of the pregnancy evolution, and some preventive measures may be indicated.…”
Section: Preeclampsia Risk Factors and Preventionmentioning
confidence: 99%
“…3 Globally, pre-eclampsia and eclampsia account for 10-15% of maternal death. 4 Most of the over half a million maternal deaths that occur annually are in the developing countries like india. 5 Eclampsia is characterized by the sudden onset of generalised tonic clonic seizures.…”
Section: Introductionmentioning
confidence: 99%